Ventricular access using skin landmarks: statistical analysis and proposal of a new ventricular entry point - RANC, Revista Argentina de Neurocirugia; Minghinelli, Federico; Bourguet, Martín; Biancardi, Mauro; Sánchez González, Federico; Zaninovich, Roberto S.; Recalde, Rodolfo (Revista Argentina de Neurocirugía, 2024)
Background: access to the lateral ventricles is widely used in neurosurgery, and ventriculostomy is a key strategy for the management of hydrocephalus and/or intracranial hypertension. Common complications include hemorrhage, infection, and catheter mispositioning, with a rate of 10-40%.Objectives: to perform radiological measurements and analysis of normal brain CT scans; and to delineate a new entry point to the ventricles from cutaneous landmarks, highlighting the potential surgical implications of these findings.Methods: six distances were measured by analyzing CT scans, which were defined as Ar: from the midline to the superficial expression of the right frontal horn; Br: from the Ad point to the right foramen of Monro; Al: from the midline to the superficial expression of the left frontal horn; Bl: from the Al point to the left foramen of Monro; C: between the nasion and a perpendicular point that passes through the foramen of Monro; and D: between point C and the foramen of Monro. Horos software was used for measurements. Minitab 18 software was used for statistical analysis based on age, sex, and side (right or left).Results: 132 brain CT scans were analyzed, yielding the following mean results: Ar distance: 2.1 cm; Br distance: 7 cm; Al distance: 2.1 cm; Bl distance: 7 cm; C distance: 12.4 cm; D distance: 7 cm; new ventricular entry point: 12.4 cm posterior to the nasion and 2.1 cm lateral to the midline.Conclusion: the freehand technique for accessing the lateral ventricles is a common neurosurgical procedure but is often accompanied by complications. To address this, we suggest a novel entry point for ventricular access, determined by cutaneous reference points. This point is situated 12.499 cm posterior to the nasion along the midline, and 2.1 cm lateral to the midline. Although our findings may play a role in presurgical planning for ventricular pathologies, future prospective studies are warranted.
Keywords: Landmarks; Skin; Statistical Analysis; Ventricles